2017
DOI: 10.1186/s13049-017-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Severity-dependent differences in early management of thoracic trauma in severely injured patients - Analysis based on the TraumaRegister DGU®

Abstract: BackgroundMajor trauma is associated with chest injuries in nearly 50% of multiple injuries. Thoracic trauma is a relevant source of comorbidity throughout the period of multiply-injured patient care and may require swift and well-thought-out interventions in order to avert a deleterious outcome. In this epidemiological study we seek to characterize groups of different thoracic trauma severity in severely injured patients and identify related differences in prehospital and early clinical management. This may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
(48 reference statements)
3
21
1
7
Order By: Relevance
“…Similar to previously published data on thoracic trauma, motorcycle crashes could be identi ed as the most frequent injury mechanism for developing a severe thoracic trauma with a clavicle fracture [11,14,29,30].…”
Section: Discussionsupporting
confidence: 71%
“…Similar to previously published data on thoracic trauma, motorcycle crashes could be identi ed as the most frequent injury mechanism for developing a severe thoracic trauma with a clavicle fracture [11,14,29,30].…”
Section: Discussionsupporting
confidence: 71%
“…Mean and upper and lower limits of the 95% confidence intervals (CI) are given. Where appropiate, the median as well as the interquartile range (IQR) are given too Parameter Pre-WBCT group ( n = 5002) WBCT group ( n = 8559) Trauma room Intubation in the trauma room [%] mean (95% CI) 55.6 [54.2–57.0] 49.3 [48.3–50.4] Chest drain in the trauma room [%] mean (95% CI) 20,0% [ 1 , 9 21 ] 18,5% [ 3 , 7 19 ] Time spent in the trauma room [minutes] mean (95% CI) median (IQR) 78 [76–79] 68 (51–87) 64 [63–65] 55 (40–77) Chest radiography [%] mean (95% CI) 85.2 [84.3–86.2] 59.8 [58.7–60.8] Trauma scan [%] mean (95% CI) 10.0 [9.2–10.8] 80.1 [79.3–81.0] Time to trauma scan [minutes] mean (95% CI) median (IQR) 31.3 [29.8–32.9] 29 (20–38) 23.6 [23.3–24.0] 21 (15–30) Discontinuation of trauma room management because of emergency surgery [%] mean (95% CI) 6.5 [5.8–7.2] 5.6 [5.0–6.1] Surgery before ICU stay [%] mean (95% CI) 44.0 [42.5–45.5] 40.5 [39.3–41.7] Further management Length of ICU stay [days] mean (95% CI) median (IQR) 10.8 [10.5–11.2] 8 (3–18) 9.7 [9.4–10.0] 6 (2–15) Length of intubation/ventilation [days] mean (95% CI) median (IQR) 6.9 [6.6–7.2] 3 (1–13) 5.6 [5.4–5.8] 2 (0–9) Length of hospital stay [days] mean (95% CI) median (IQR) 26.2 [25.8–26.9] 23 (11–37) 23.3 [22.7–23.8] 17 (9–30) Ventilator-free days [days] mean (95% CI) median (IQR) 19.8 [19.4–20.1] 24 (2–29) 20.8 [2...…”
Section: Resultsmentioning
confidence: 99%
“…Thoracic injuries account for 25% of deaths in polytrauma patients and are thus a common cause of death among these patients [ 1 , 2 ]. In recent years, a trauma room algorithm has become widely accepted in Germany which is based on Advanced Trauma Life Support (ATLS ® ) and the European Trauma Course [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a minority of patients with thoracic trauma tends to develop respiratory failure requiring intubation and ventilator support to correct hypoxia and hypercapnia [ 3 ]. On the other hand, 35 to 58% of severely injured patients require prehospital intubation, depending on the severity of concomitant chest injury [ 4 , 5 ]. While severely injured patients usually require intensive care therapy irrespective of accompanying thoracic injuries, organ dysfunction and multiple organ failure (MOF) are known to develop more often in patients with severe thoracic trauma [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking care of a severely injured patient is demanding. Differences in prehospital and early clinical trauma management have been reported that depends on the severity of an accompanying chest trauma [ 5 ]. Multiply-injured patients with blunt chest trauma require significantly longer periods of mechanical ventilation and a significantly longer stay in the ICU than trauma patients without a thoracic injury [ 2 ].…”
Section: Introductionmentioning
confidence: 99%